Diversity of Soil Fauna and It’s Role in Litter Decomposition of Oil Palm (Elaeis guineensis Jacq) - Noor Farikhah Haneda; Betti Andriany Sirait (Jurnal Silvikultur Tropika, 2012)
Indonesia is rich country of biodiversity. Forest is a natural habitat for soil fauna incontinuity it’s life. Information about soil fauna in Indonesia and it’s role in litter decomposition is still limited, so that necessary research of soil fauna diversity and it’s role in decomposition process. This research was done in October 2009 to February 2010. Inventarisation of macro diversity and soil meso fauna with funnel extraction tecnic Berlease. Furthermore, rate calculation of decomposition was done. The result show that species richness value generally between 1.61-3.11, diversity value is generally between 1.49-2.13 while evenness value is generally between 0,45-0,65. Soil fauna diversity of oil palm litters included medium level. Base on  inventarisation result there are 11  ordo in soil fauna of oil palm land, 17 families with 26 morphospecies, while amount of soil fauna that was found  is 237 individuals. After percentage ranking the highest to the smallest, this land type is dominated by Acari, Collembola and Hymenoptera (family Formicidae). Based on the decomposition rate data was obtained, the rate of decomposition for each  harvest time (over 2 weeks) varies in the range 0.80-1.44%/hari. The rate of decomposition of the most quickly is found on the 2nd harvest where the rate of decomposition reach 44%/hari. The results of statistical analysis was obtained stated time with influential positions in the real rate of litter decomposition of oil palm.